Pre-practice hydration status in soccer (football) players in a cool environment - Kiitam, U.; Voitkevica, L.; Timpmann, S.; Pontaga, I.; Ereline, J.; Unt, E.; Ööpik, V. (Medicina, 2018)
Background and Objectives: Only a few studies have reported the pre-practice hydration status in soccer players (SPs) who train in a cool climate. The primary purpose of this study was to examine the hydration status of male semiprofessional SPs immediately before their regular training session in winter. The secondary purpose was to compare the urinary indices of the hydration status of Estonian and Latvian SPs. Materials and Methods: Pre-training urine samples were collected from 40 Estonian (age 22.1 ± 3.4 years, soccer training experience 13.7 ± 3.9 years) and 41 Latvian (age 20.8 ± 3.4 years, soccer training experience 13.3 ± 3.0 years) SPs and analyzed for urine specific gravity (USG). The average outdoor temperature during the sample collection period (January-March) was between -5.1 °C and 0.2 °C (Estonia) and -1.9 °C and -5.0 °C (Latvia). Results: The average pre-training USG of Estonian and Latvian SPs did not differ (P = 0.464). Pooling the data of Estonian and Latvian SPs yielded a mean USG value of 1.021 ± 0.007. Hypohydration (defined as a USG = 1.020) was evident altogether in fifty SPs (61.7%) and one of them had a USG value greater than 1.030. Conclusions: Estonian and Latvian SPs do not differ in respect of USG and the prevalence of pre-training hypohydration is high in this athletic cohort. These findings suggest that SPs as well as their coaches, athletic trainers, and sports physicians should be better educated to recognize the importance of maintaining euhydration during the daily training routine in wintertime and to apply appropriate measures to avoid hypohydration.